Implementation of Progressive Law in Post-Divorce Alimony Rights in Obscuur Libel Verdict (Case Study of Decision No. 2276/Pdt.G/2023/PA.Bgl) - Falakh, Mokhamad Fajrul (Sakina: Journal of Family Studies, 2025)
The case that occurred at the Bangil Religious Court with Number: 2276/Pdt.G/2023/PA.Bgl. In the lawsuit, the plaintiff sued cumulatively with the support of the wife after the divorce and child support. However, the Panel of Judges rejected all lawsuits about alimony rights filed by the plaintiff against the defendant and only granted the divorce lawsuit because of the lawsuit about obscuur libel alimony rights. The analysis used using the perspective of progressive law Sajtipto Rahardjo is related to justice in deciding divorce cases with the right to support the wife and children after the divorce which was rejected on the grounds of the obscuur libel lawsuit. The purpose of this study is to analyze and describe how the decision Number: 2276/Pdt.G/2023/PA. Bgl whether it is in accordance with positive law in Indonesia and uses the perspective of Prarogresive Law of Satjipto Rahardjo. The result of this investigation is that the verdict is not in line with the positive law and the progressive law of Satjipto Rahardjo. In deciding a case, it is not only based on dogma-normatives but also must consider justice and conscience in decideing. The decision does not meet the elements in the perspective of Satjipto Rahardjo's Progressive Law, namely flexibility, social justice, human rights, and change. This can be seen from the decision which only looks at the formal aspect of the lawsuit, does not give the rights that should be given to the wife and children, does not provide justice to the victim, and does not provide a change for the better after the case is decided.